Individual tree parameter extraction at the plot level in tropical forest using terrestrial laser scanning / Nur Irdina Zulaika Abu Badri - Abu Badri, Nur Irdina Zulaika (2022)
Forests are essential among the resources because they provide a source of wood as well as a means of protecting the hills, regulating streamflow, and minimizing soil erosion, among other things. Forests can only provide maximum advantages and benefits if they are managed appropriately. The quantity and quality of data available about the forest are crucial to effective forest management. If a renewable natural resource like a forest is to be managed reasonably and sustainably, basic data and information are essential. Forest inventories are the source of this data. This study aims to assess individual tree parameter extraction at the plot level in Tropical Forest using Terrestrial Laser Scanning (TLS). In order to achieve this study, there are two objectives of this research which are to establish the data collection of tree attributes such as tree species, tree height, diameter at breast height (DBH) using conventional method and terrestrial laser scanning and to identify the performance of Vision Lidar software and Cloud Compare software in generating the individual tree quantification. The method involved in the data processing used Vision Lidar and Cloud Compare software to process digital data and do the processing. This study will help the data of the tree characteristic to be kept updated using advanced technology. As a result, in terms of equipment purchase costs, staff skills and qualifications, data collecting working time, data recording accuracy, post-processing time, and labor expenses, one can select the most cost-effective approach for gathering forestry reference data. Although the application of TLS in forest inventory is a promising technology.